Estrogen anti‐inflammatory activity on human monocytes is mediated through cross‐talk between estrogen receptor ERα36 and GPR30/GPER1. Issue 2 (22nd September 2015) - Pelekanou, Vasiliki; Kampa, Marilena; Kiagiadaki, Foteini; Deli, Alexandra; Theodoropoulos, Panayiotis; Agrogiannis, George; Patsouris, Efstratios; Tsapis, Andreas; Castanas, Elias; Notas, George
Abstract : Ligand‐activated ER, ERα36, inhibits LPS‐induced IL‐6 expression in human monocytes via inhibition of NFκB transcriptional activity, in a GPR30/GPER1‐dependent manner. Abstract : Estrogens are known modulators of monocyte/macrophage functions; however, the underlying mechanism has not been clearly defined. Recently, a number of estrogen receptor molecules and splice variants were identified that exert different and sometimes opposing actions. We assessed the expression of estrogen receptors and explored their role in mediating estrogenic anti‐inflammatory effects on human primary monocytes. We report that the only estrogen receptors expressed are estrogen receptor‐α 36‐kDa splice variant and G‐protein coupled receptor 30/G‐protein estrogen receptor 1, in a sex‐independent manner. 17‐β‐Estradiol inhibits the LPS‐induced IL‐6 inflammatory response, resulting in inhibition of NF‐κB transcriptional activity. This is achieved via a direct physical interaction of ligand‐activated estrogen receptor‐α 36‐kDa splice variant with the p65 component of NF‐κB in the nucleus. G‐protein coupled receptor 30/G‐protein estrogen receptor 1, which also physically interacts with estrogen receptor‐α 36‐kDa splice variant, acts a coregulator in this process, because its inhibition blocks the effect of estrogens on IL‐6 expression. However, its activation does not mimic the effect of estrogens, on neither IL‐6 nor NF‐κB activity. Finally, we show that the estrogen receptor profile observed in monocytes is not modified during their differentiation to macrophages or dendritic cells in vitro and is shared in vivo by macrophages present in atherosclerotic plaques. These results position estrogen receptor‐α 36‐kDa splice variant and G‐protein coupled receptor 30 as important players and potential therapeutic targets in monocyte/macrophage‐dependent inflammatory processes.